Quality by Design Approach for the Development and Validation of a Robust RP-HPLC Method for the Estimation of Aloe-emodin - Husain, Muzammil; Agrawal, Yogeeta O. (Current Pharmaceutical Analysis, 2024)
Introduction/ObjectiveThe current study examines the methodical Quality by Design (QbD) that facilitated the creation of an easy-to-use, quick, affordable, and stability-indicating reversed-phase high-performance liquid chromatography (RP-HPLC) technique for the efficient analysis of aloe-emodin.MethodsThe chromatographic conditions were optimized with the Design Expert software 11.0 version, i.e., flow rate, buffer concentration, and column temperature.ResultsThe results of the linearity graph show R2 = 0.9988. The LOQ was 0.07949 µg/mL and the LOD was 0.02623 µg/mL. According to ICH rules, the technique validation parameters were within the allowed range. Utilizing the Design Expert 11.0 version, the Box–Behnken design experimental design explains the relationships between flow rate, buffer concentration, and column temperature at three distinct levels. The responses were monitored: the retention time (Rt), tailing factor (Tf), and number of theoretical plates (NTPs).ConclusionThe suggested approach was appropriate for quantitative determination and may be used in clinical pharmacokinetic investigations, biopharmaceutics, accredited testing laboratories, and quality control departments in enterprises.
Keywords: stability-indicating method